2020
DOI: 10.2224/sbp.9356
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and student creativity: The mediating role of student engagement

Abstract: Fostering student creativity is widely accepted as an important goal in Chinese higher education, and social media is now integrated into students' everyday lives. I investigated how social media use in study contexts is related to students' engagement and creativity. A validated questionnaire was used to collect data from 652 undergraduate students at 3 Chinese public universities. Structural equation modeling results show that social media use in study contexts was related to student engagement and creativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The prevalence of the internet, social networks, and even photo, video and text editing software for a more organized online presence, require the knowledge and management of different technologies. Furthermore, the study by Sun [37] shows students' tendency to generate new ideas, which could be useful for production and service implementations, and also for the interactive exchange of the information, all of which require fine knowledge of ICT skills.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the internet, social networks, and even photo, video and text editing software for a more organized online presence, require the knowledge and management of different technologies. Furthermore, the study by Sun [37] shows students' tendency to generate new ideas, which could be useful for production and service implementations, and also for the interactive exchange of the information, all of which require fine knowledge of ICT skills.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an empirical study conducted by Yang (2021) on 466 practitioners also showed a positive correlation between personal work engagement and creativity. Similarly, Sun (2020) survey of 652 university students showed that student engagement moderated the relationship between social media use and student creativity.…”
Section: Literature Reviewmentioning
confidence: 98%
“…An interactive distance learning environment located on the Internet and this environment mimic the usual physiological class, in terms of its elements and the classroom interactions and teaching strategies used by the teacher to teach and learn particular curriculum e-learning tools such as e-mail, textile network, discussion groups, file transfer, participatory whiteboard [6].…”
Section:  the Concept Of Social Media In Educationmentioning
confidence: 99%